Prophetic Change Management and Strategic Failure: A Qur’anic Framework from Surah Ash-Shu‘arā’ - Muhammad Aamir Ali; Nazish Aamir; Ahmed Ali Jamil (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2026)
This study develops a Qur’an-informed strategic change management framework grounded in the prophetic narratives of Surah Ash-Shu‘arā’, addressing a critical gap in contemporary strategic management literature regarding the ethical foundations of long-term success and failure. Using qualitative thematic coding combined with network centrality analysis, the study maps key constructs—ethical vision, change enablers, stakeholder response, change duration, strategic outcomes, and moral accountability—and examines their structural relationships across prophetic cases. The findings reveal that strategic outcomes function as mediating consequences rather than direct results of authority or symbolic power, with moral accountability and stakeholder response emerging as central determinants of change trajectories. Network metrics demonstrate that resistance to ethical reform, when sustained over time, systematically precedes institutional collapse, while ethical legitimacy and principled leadership underpin strategic resilience. Prophetic figures operate as carriers of a universal ethical–strategic logic, emphasizing process integrity over individual charisma. By translating Qur’anic moral causality into a replicable strategic framework, this study contributes to ethical governance, institutional theory, and value-based leadership research. The findings offer actionable implications for leaders and policymakers, highlighting ethical accountability as a strategic asset and early moral warnings as critical risk signals. The study advances a novel interdisciplinary bridge between Qur’anic ethics and contemporary strategic change management theory.